A HERITAGE TO OPEN MORE CONVERSATIONS, THE CASE OF IDA BAGUS NJANA’S DEWI PERTIWI SCULPTURES - Dewa Ayu Eka Savitri Sastrawan (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2021)
In the midst of the 2020 pandemic, an intriguing writing project landed. It was uncertain how it could be done with all the restrictions, as the project requires involvement of a heritage that needs to be observed directly. Yet gradually it leads to encouraging better understanding of our position as humans in this current situation. The heritage was Ida Bagus Njana’s sculptures. Njana is a well-known sculptor from Mas Village, Ubud, Gianyar, Bali. His works have been said to be the start of modern Balinese sculptures, especially his wood works. Very little of his works still exist in Bali, namely in his own family museum Njana Tilem Museum, then Museum Puri Lukisan, Pura Taman Pule temple, and Taman Werdhi Budaya. Existing writings on Njana lie in the existence of Pita Maha, the community or group of painters and sculptures in the 1930s. However, when conversations took place with his family in 2020, Njana’s sculptures were not merely an artwork to be sold, it’s filled with spiritual thinking and expressions. His works with the title “Dewi Pertiwi” (meaning: Goddess of Earth) are filled with surrealism - not only its elegant carved shapes being different from the traditional Balinese methods, but also its mysterious narration about the Goddess itself. It was later observed that these narrations were not that mysterious. It actually came from Njana’s knowledge from scriptures (lontar), which means he really thought through what he was expressing about the Goddess of Earth narratives. These “Dewi Pertiwi” sculptures speak of the environment and earth that we live in and serve as somewhat reminders. This then inspired us to continue the conversation of appreciating and understanding these narrations with our current life. And interestingly landed as a curatorial project “Pertiwi” with the theme resilience in a form of website, where Njana’s Dewi Pertiwi sculptures were part of its starting point.